Branding Strategy for Local Basketball Clubs Through Social Media Among Gen Z: A Literature Study - Putra, Dio Kurniawan Oktav Jasya; Marpaung, Deni Rahman; Sihotang, Fadhil; Manihuruk, Kevin Owen; Siregar, Reynaldi; Ginting, Haikel Pranata (Universitas PGRI Palembang, 2025)
The development of digital technology has revolutionized the way local sports clubs build brand identity and interact with their audiences, especially Generation Z, which is the most dominant group of social media users today. This research aims to examine the branding strategies implemented by local basketball clubs through social media platforms to build engagement and loyalty among Gen Z. The methods used include literature review and secondary data analysis of the social media activities of three local basketball clubs on TikTok, Instagram, and Twitter. The analysis results show that TikTok and Instagram are the most effective media in reaching Generation Z, marked by high engagement rates in the form of likes, comments, and content sharing. In contrast, Twitter shows lower engagement levels. This research concludes that the success of branding strategies lies in the utilization of creative, authentic visual content that aligns with the values and communication style of Gen Z. These findings provide practical implications for local basketball clubs in designing relevant and impactful digital approaches in the era of social media-based marketing.